Hysteretic performance of stainless steel double extended end-plate beam-to-column joints subject to cyclic loading. (July 2021) - Gao, J.D.; Du, X.X.; Yuan, H.X.; Theofanous, M.
Abstract: This paper focuses on the hysteretic performance of stainless steel beam-to-column joints with double extended end-plate connections under cyclic loading. Six full-scale joint specimens were fabricated, including three interior column joints and three exterior column joints. Two stainless steel grades — austenitic grade EN 1.4301 and duplex grade EN 1.4462, and one carbon steel grade Q345B were considered. A4-80 stainless steel bolts and grade 10.9 high strength steel bolts were employed to assemble the joint specimens. The cyclic loading tests were conducted using the loading protocol set in Chinese standard JGJ/T 101. The force versus displacement ( F - Δ ) hysteresis curves were recorded, and the failure modes, the ductility, the strength and stiffness degradation, and the energy dissipation capacity of the tested joints were analysed and discussed in detail. Empirical hysteresis models were developed and calibrated against the recorded hysteretic curves and energy dissipation capacities of the tested joints. The experimental results involving the initial rotational stiffness values and the moment resistances were further utilised to evaluate the accuracy of current design provisions codified in EN 1993-1-8, ANSI/AISC 358 and GB 51022. The comparison shows that the development of accurate design guidance accounting for the pronounced strain hardening of stainless steels is warranted. Highlights: Cyclic loading tests on six stainless steel and carbon steel end-plate joints. Stainless steel joints exhibit better hysteretic performance than carbon steel ones. Rotations of tested joints exceed ductility demands in seismic design standards. Assessment of predictions from European, American and Chinese design codes.